The Lexical Density of Erlanggaâ€™s â€œEnglish On Skyâ€ Analysis - Ramadhan, Gagang; Santihastuti, Asih; Wahjuningsih, Eka (Universitas Jember, Indonesia, 2017)
The aims of this research were to know whether the reading texts found in â€œEnglish On Skyâ€ textbook for 8th Grade of Junior High School were appropriate and meet the content of the curriculum or not by analyzing the lexical density of its texts and identifying the type of reading text which should be given based on the KTSP curriculum. The research design used was descriptive qualitative research. The instrument of this research was document which was get from collecting the reading texts found in the textbook. The data in this study was analyzed quantitatively in the form of description and used descriptive statistics for describing the features of data. The result of this result was there was no reading text in the textbook that was categorized as high lexical density. The readi ng texts were categorized as low and moderate lexical density as there were 12 reading texts were categorized as low lexical density and 12 reading texts were categorized as moderate lexical density. 12 reading text that categorized as low lexical density had 40% - 50% lexical density percentage. On the contrary 12 reading texts that categorized as moderate lexical density had 50% - 60% lexical density percentage. The highest percentage of the lexical density reading text found in the textbook was 57.72% entitled â€œCampingâ€. Meanwhile, the lowest percentage of the lexical density reading text was 41.61% entitled â€œNone of your business!â€. Based on the analysis, the genre found in this textbook were descriptive, recount, and narrative. In conclusion, this textbook were easy enough to understand for student and met the content of school-based curriculum. Keywords: Descriptive Qualitative Research, Discourse Analysis, Lexical Density, Reading Text